PELARUTAN TERAK TIMAH BANGKA MENGGUNAKAN LARUTAN NaOH [Dissolution Of Tin Slag Bangka Using NaOH Solution] - Suharyanto, Ariyo; Sulistiyono, Eko; Firdiyono, F (Jurnal Metalurgi, 2014)
Tin slag from tin ore concentrate smelting process is a product that has the potential to be developed, especially rare earth elements (REE). Therefore, the purpose of this study is to determine the solubility of tin slag secondary minerals in NaOH solution. Tin slag taken from two tin slag furnaces such as tin slag I and II that were obtained from lead smelting process of phase I and II in Bangka Island. In this study, the raw material used was tin slag I and II, which has been roasted at a temperature of 700°C and 900°C, and then dissolved in NaOH solution. The solids (residue) obtained from dissolution experiments with NaOH were analyzed by XRD (X-ray diffraction) and XRF (x-ray fluorescence). Dissolution results showed that the solubility of tin slag was about 10% and 5 % for tin slag II and I, respectively. XRF results indicated that elements in the tin slag dissolved in NaOH solution were amphoteric elements such as tin, silica, alumina, titania and zirconia.